Biotechnological production of cyclic dinucleotides—Challenges and opportunities. Issue 3 (4th January 2022) - Bartsch, Tabea; Becker, Martin; Rolf, Jascha; Rosenthal, Katrin; Lütz, Stephan
Abstract: Cyclic dinucleotides (CDNs) are widely used secondary signaling molecules in prokaryotic and eukaryotic cells. As strong agonists of the stimulator of interferon genes, they are of great interest for pharmaceutical applications. In particular, cyclic‐GMP‐AMP and related synthetic CDNs are promising candidates in preclinical work and even some in clinical phase 1 and 2 studies. The comparison of chemical and biocatalytic synthesis routes elucidated that biological CDN synthesis offers some advantages, such as shorter synthesis time, avoiding complex protective group chemistry, and the access to a new spectrum of CDNs. However, the synthesis of CDNs in preparative quantities is still a challenge, since the chemical synthesis of CDNs suffers from low yields and complex synthetic routes and the enzymatically catalyzed synthesis is limited by low product titers and process stability. We aim to review the latest discoveries and recent trends in chemical and biocatalytic synthesis of CDNs with a focus on the synthesis of a huge variety of CDN derivatives. We furthermore consider the most promising biotechnological processes for CDN production by evaluating key figures of the currently known processes. Abstract : In this review, recent discoveries and trends in the chemical and biocatalytic synthesis of cyclic dinucleotides (CDNs) are presented. Interest in the synthesis of CDNs, especially cGAMP and cGAMP‐related synthetic CDNs, is high due to their potential for pharmaceutical applications. Therefore, the authors address the most promising chemical and biocatalytic synthesis routes for CDN production by evaluating the key data of currently known processes and discussing the challenges and limitations of synthesizing CDNs in preparative amounts.